Cured shape prediction of fiber metal laminates considering interfacial interaction. (15th June 2018) - Che, Lu; Zhou, Zhengong; Fang, Guodong; Ma, Yunfei; Dong, Wenzhe; Zhang, Jiazhen
Abstract: During the manufacturing process of fiber metal laminates (FMLs), incompatible residual strain leads to the problem of slippage interaction at the interface between the metal layer and the fiber layer. An analytical model and finite element (FE) model considering slippage effect are established to obtain the cured shape and deformation of cross-ply [Al/0/90/Al] FMLs. Both analytical and FE results are in good agreement with experimental results. The predicted models proposed in this paper can accurately and effectively calculate the equilibrium configurations of FMLs at room-temperature. In order to reveal the curing deformation characteristics of FMLs, the influence laws of geometry dimensions and metal ply thickness on the cured stable shapes are obtained by using the prediction models for the square and rectangular laminates.